Pengaruh Gerak U-Turn Terhadap Kinerja Lalu Lintas Di Ruas Jalan Pomalaa (Studi Kasus : Jalan Jendral Sudirman Kelurahan Dawi-Dawi) - Al Tafakur Laode; Muh. Ismail Syafar; Bagus Eko Prasetyo; Khairil Ibrahim (MEDIA KONSTRUKSI, 2024)
One way to facilitate the movement of vehicle traffic is to provide a median opening as a vehicle U-Turn facility. With the u-turn facility, it has an impact on the movement of vehicles in the direction and opposite to the u-turn. A rotating vehicle causes an increase in the volume of the vehicle in the opposite direction. In addition, vehicles that rotate will slow down and form a queue when approaching a u-turn. Vehicles that make a U-turn also need time to pass through the u-turn facility and then converge with the flow of vehicles in the opposite direction. Some of these things show the influence of u-turn facilities on road performance. The study was conducted on a u-turn located in Pomalaa, Dawi-Dawi sub-district, which passed the u-turn for 3 days, namely Monday, Wednesday and Sunday The observation time used in the study was morning at 07.00.08.00 – 08.00.09.00 WITA, afternoon at 12.00.13.00 - 13.00.14.00 WITA, and afternoon at 16.00 – 17:00. – 17.00.18.00 WITA. After calculations were carried out by analyzing data on Monday, the highest traffic volume that made a u-trun in the Tanggetada direction had a degree of saturation (DJ) which was = 0.15 meaning that there was a delay when the vehicle did u-trun had a very good service level or did not exceed 0.85 according to PKJI 2014 standards.and the degree of saturation (DJ) on Monday in the highest Wundulako direction = 0.11. Then the highest side obstacles on Monday in the Wundulako direction with the number of events = 581.1 indicate that the side obstacles fall into the category (T) high, for the highest straight-way traffic volume on Monday namely the direction of Wundulako = 663.85 and the direction of Tanggetada = 596.6. The biggest delay occurred on Monday at 07.00-08.00 amounting to 3.67 sec/skr.